PRELIMINARY FINDINGS ON GROWTH PERFORMANCE OF Chrysichthys nigrodigitatus UNDER DIFFERENT CULTURE CONDITIONS - ANWA-UDONDIAH, E. P; ANYANWU, P. E.; OGUNTADE, O. R.; AJIJO, M. R. (Nigerian Journal of Fisheries, 2012)
A study was conducted to compare the growth performance of fingerlings of the silver catfish Chrysichthys nigrodigitatus in fibre-glass tanks and earthen ponds for eight weeks. One hundred and forty-four fingerlings of C. nigrodigitatus with a mean weight of 3 g obtained from the wild were stocked in triplicates and differences in growth indices were determined at the completion of the study. Silver catfish reared in earthen ponds gained more weight than their counterparts in the fibre-glass tanks. Final mean weight of the tank and pond reared catfish were 10.237 ± 1.23 g and 17.698 ± 0.17 g respectively. The mean weight increase of pond reared fish was significantly higher (P < 0.05) at 176%. The specific growth rate of the pond reared catfish was 3% while that of the tank reared was 2%. This study demonstrated improved growth performance of pond reared Chrysichthys nigrodigitatus.